Analisis Regresi Logistik Multinomial pada Faktor-Faktor yang Mempengaruhi Perilaku Penumpang (Studi Kasus Penumpang Bogor terhadap Perubahan Stasiun Manggarai) - Dien-Muhammad, Mirai Annabila; Naipospos, Binsar Parasian (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2024)
Manggarai Station is planned to be central of public transportation in Jakarta. Commuter line or known as KRL is one of the modes offered at the station and has served trips and become a favorite mode of Jabodetabek commuters. The planning requires a switchover transition, which impacts Manggarai Station in the form of changes in routes and infrastructure. This also has an impact on commuter travel behavior. This study aims to identify variables that relate and affect commuter travel behavior towards changes at Manggarai Station. Methods were conducted with chi-square and multinomial logit analysis on a sample of 400 commuters through questionnaire data. The results show that the factors associated with changes in passenger behavior are marital status, education, income, location of residence, number of cars and motorbike owned, origin station, alternative modes used, destination line, transit frequency, travel frequency, waiting time, overall travel time, KRL travel time, mode used and changes in other passenger behavior. In addition, factors that have a significant effect of 34.6% on changes in commuter travel behavior are the location of residence (Bogor City), origin station (Cilebut Station and Bojong Gede Station), the mode used (public transportation), KRL travel time (100-199 minutes) and awareness of changes in other passenger behavior. Meanwhile, the other 65.4% is influenced by independent variables outside the study.